Analysis of university attitudes about political leaders, institutions, authorities, values, Peru and historical characters - Montero López, Víctor (2019)
Through a survey applied to young people from a national university, they associated different words to detect their attitudes about political leaders, institutions, media, authorities, values, Peru and historical figures, negative valuations prevail over each of them , with few exceptions. In general, the answers allow us to detect that their attitudes relate the problems to a crisis of political parties, political leaders, government and political regime. The characters most associated with the fight against corruption are more valued. It was also detected which are the most admired Peruvians in history and nowadays, indicating positive and negative aspects of Peru and the diverse values of Peruvians.